Positive electrode active material, preparation method thereof and lithium ion battery
Through the combined sintering technology of nickel, cobalt, manganese and other elements, doped elements and M2Se3, a positive electrode active material with high magnification performance and structural stability was prepared, which solved the capacity attenuation of existing materials under high magnification conditions and The polarization problem has achieved improvement in battery performance and cost control.
Patent Information
- Application Number
- CN202411629772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing positive electrode active materials of lithium-ion batteries show fast capacity attenuation and serious polarization under high-rate charging and discharge conditions, resulting in a decline in battery performance and cannot meet the requirements of automotive micro-hybrid batteries for rate performance.
Co-precipitation reaction is carried out using nickel sources, cobalt sources, manganese sources, doping elements, urea, alcohol solvents and water. After multiple sintering treatments, a positive electrode active material with a high aspect ratio is prepared and included in the material. M2Se3 was introduced to improve electron conductivity and structural stability.
The prepared cathode active material has excellent high rate performance and structural stability, can maintain high capacity under large-scale and low temperature conditions, and has low production costs, making it suitable for large-scale promotion and application.
Smart Images

Figure CN119160954A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a positive electrode active material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the rapid development of science and technology and the continuous expansion of the market for portable electronic devices, electric vehicles, etc., higher and higher requirements are put forward for key indicators such as energy density, cycle life and rate performance of lithium-ion batteries. For example, automotive micro-hybrid batteries require an instantaneous discharge rate greater than or equal to 20C and a cycle performance greater than or equal to 3000 weeks. However, the existing lithium-ion battery positive electrode active materials still have significant deficiencies in rate performance, which has become a bottleneck problem restricting the further application and development of lithium-ion batteries.
[0003] Specifically, the rate performance of lithium-ion batteries mainly depends on the electronic conductivity, ion diffusion rate and material structure stability of the positive electrode active material. Although the existing positive electrode active materials have met the market demand for lithium-ion batteries to a certain extent, they often show problems such as rapid capacity decay and severe polarization under high-rate charge and discharge conditions, resulting in a decrease in the overall performance of the battery.
[0004] Therefore, the development of new lithium-ion battery positive electrode active materials with high rate performance has become a research hotspot and urgent need in the current lithium-ion battery field. Summary of the invention
[0005] The purpose of the present application is to provide a positive electrode active material and a preparation method thereof and a lithium ion battery to solve the above problems.
[0006] To achieve the above objectives, this application adopts the following technical solutions: A method for preparing a positive electrode active material, comprising: Mixing a nickel source, a cobalt source, a manganese source, a compound containing a doping element, urea, an alcohol solvent and water, and performing a coprecipitation reaction to obtain a first intermediate, wherein the doping element in the compound containing a doping element includes any one of Zr, Al, W, Sr and B; The first intermediate is mixed with a lithium source and subjected to a first sintering treatment to obtain a second intermediate; The second intermediate is mixed with M2Se3 and subjected to a second sintering treatment to obtain a positive electrode active material, wherein M in the M2Se3 includes any one of In and Ga. According to an embodiment of the present application, based on the total mass of the nickel source, the cobalt source, and the manganese source, the added amount of the compound containing the doping element is 1000-3000 ppm.
[0007] According to an embodiment of the present application, the nickel source includes any one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate; The cobalt source includes any one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate; The manganese source includes any one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; The molar ratio of nickel in the nickel source to cobalt in the cobalt source and manganese in the manganese source is x:y:(1-xy), wherein 0 <x≤0.60,0<y≤0.40; And / or, the ratio of the molar amount of the urea to the sum of the molar amounts of the nickel source, the cobalt source, and the manganese source is (1-2):1; And / or, the alcohol solvent includes at least one of ethanol, propanol, and isopropanol; And / or, the mass ratio of the alcohol solvent to the water and the urea is 1.5:1:(1-1.5).
[0008] According to an embodiment of the present application, the temperature of the coprecipitation reaction is 70-95°C; And / or, the coprecipitation reaction time is 2 to 5 hours; And / or, when preparing the first intermediate, the method further comprises: continuously introducing an inert gas below the liquid surface of the reaction system, wherein the inert gas comprises at least one of nitrogen, argon, helium and neon.
[0009] According to an embodiment of the present application, the lithium source includes at least one of LiOH, Li2CO3, CH3COOLi, Li2C2O4, LiF, and Li3PO4; And / or, the molar ratio of the first intermediate to the lithium source is 1:(1.05-1.2).
[0010] According to an embodiment of the present application, the first sintering treatment includes: sintering at a temperature of 300-600°C for 2-6h, then sintering at a temperature of 650-750°C for 2-6h, sintering at a temperature of 800-950°C for 10-20h, and then reducing the temperature to room temperature; And / or, the heating rate of the first sintering treatment is 1-5°C / min, and the cooling rate of the first sintering treatment is 1-5°C / min; And / or, the first sintering process is performed in an oxygen atmosphere.
[0011] According to an embodiment of the present application, based on the mass of the second intermediate, the mass of the M element in the M2Se3 is 800-1500 ppm.
[0012] According to an embodiment of the present application, the temperature of the second sintering treatment is 290-400° C., and the time of the second sintering treatment is 8-12 hours.
[0013] The present application also provides a positive electrode active material, which is prepared by the preparation method of the positive electrode active material described above.
[0014] The present application also provides a lithium-ion battery, which includes the positive electrode active material described above.
[0015] Compared with the prior art, the beneficial effects of this application include: The first intermediate prepared in the present application has a petal-like shape, a large specific surface area and a loose structure, which is beneficial to Li + The primary particles formed by diffusion and material primary particle formation are rod-shaped with a very high aspect ratio. The high aspect ratio is beneficial to the Li + Insertion / extraction, providing faster Li + The diffusion rate is beneficial to the capacity of the positive electrode material under high rate and low temperature conditions.
[0016] The doping element compound used in the preparation method of the present application can introduce the doping element, which has the function of supporting the layered structure and anchoring, and is conducive to improving the structural stability of the positive electrode active material. The M2Se3 introduced in the present application has the function of improving the electronic conductivity. The positive electrode active material prepared in the present application has an extremely high aspect ratio, Li + The escape path is extremely short, and the positive electrode active material has excellent high rate performance. In addition, the method of the present application has the advantages of simple operation and low production cost, which is conducive to large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0018] Figure 1 is a SEM image of the first intermediate in Example 1; Figure 2 is a SEM image of the positive electrode active material in Example 1; Figure 3 is a SEM image of the positive electrode active material in Example 2; Figure 4 is a SEM image of the positive electrode active material in Example 3; Figure 5 is a SEM image of the positive electrode active material in Example 4; Figure 6 is a SEM image of the first intermediate in Example 5; Figure 7 is a SEM image of the positive electrode active material in Example 5; Figure 8 is a SEM image of the positive electrode active material in Example 6; Fig. 9 is a SEM image of the positive electrode active material in Example 7; Fig.10 This is a SEM image of the positive electrode active material in Comparative Example 1; Fig.11 is a SEM image of the first intermediate in Comparative Example 2; Fig.12 This is the SEM image of the positive electrode active material in Comparative Example 2. DETAILED DESCRIPTION
[0019] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0020] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0021] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0022] In these examples, parts and percentages are by mass unless otherwise indicated.
[0023] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0024] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0025] The present application provides a method for preparing a positive electrode active material, comprising: Mixing a nickel source, a cobalt source, a manganese source, a compound containing a doping element, urea, an alcohol solvent and water, and performing a coprecipitation reaction to obtain a first intermediate, wherein the doping element in the compound containing a doping element includes any one of Zr, Al, W, Sr and B; The first intermediate is mixed with a lithium source and subjected to a first sintering treatment to obtain a second intermediate; The second intermediate is mixed with M2Se3 and subjected to a second sintering treatment to obtain a positive electrode active material, wherein M in the M2Se3 includes any one of In and Ga. The preparation method of the present application uses a compound containing doped elements, and the doped elements can play a role in supporting the layered structure and anchoring, which can effectively inhibit the expansion / contraction of the unit cell along the c-axis direction during the charge and discharge process, reduce the volume and stress changes, and slow down the decay of the internal structure of the positive electrode active material during the charge and discharge process. Moreover, the present application uses a liquid phase method to prepare the first intermediate, which can make the doped elements evenly distributed in the first intermediate, avoiding the occurrence of undesirable problems such as agglomeration and uneven dispersion of doped elements, element loss, and decreased unit cell structure optimization effect that occur in traditional solid phase mixtures.
[0026] Moreover, in the present application, urea is added as an initiator when preparing the first intermediate, and there is no need to add NaOH or irritating ammonia water. This step has the advantages of mild reaction conditions, good control of the synthesis process, and simple operation.
[0027] Using the method of the present application, M2Se3 can be coated on the surface of the second intermediate. As a two-dimensional layered material, M2Se3 has a small energy gap, strong tunability, and high carrier mobility. M2Se3 can increase the electron transmission rate, inhibit the initial and cycle DCR growth, and improve the high-rate performance of the material, which is beneficial to improving the rate performance of the positive electrode active material. Moreover, M2Se3 can also stabilize the two-phase interface, which can avoid direct contact between the positive electrode active material and the electrolyte during the cycle, reduce the occurrence of side reactions and the corrosion of the material surface by harmful substances such as HF generated during the reaction, and avoid accelerated electrolyte consumption in the scenario of high-rate discharge, thereby improving the cycle stability of the positive electrode material. In addition, M2Se3 also has good thermal stability and chemical stability, which is beneficial to improving the structural stability of the positive electrode active material.
[0028] According to an embodiment of the present application, based on the total mass of the nickel source, the cobalt source, and the manganese source, the added amount of the compound containing the doping element is 1000-3000 ppm.
[0029] For example, based on the total mass of the nickel source, the cobalt source and the manganese source, the added amount of the doping element-containing compound can be 1000ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 2000ppm, 2500ppm, 3000ppm or any value between 1000 and 3000ppm.
[0030] According to an embodiment of the present application, the nickel source includes any one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate; The cobalt source includes any one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate; The manganese source includes any one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; The molar ratio of nickel in the nickel source to cobalt in the cobalt source and manganese in the manganese source is x:y:(1-xy), wherein 0 <x≤0.60,0<y≤0.40; And / or, the ratio of the molar amount of the urea to the sum of the molar amounts of the nickel source, the cobalt source, and the manganese source is (1-2):1; For example, the ratio of the molar amount of the urea to the sum of the molar amounts of the nickel source, the cobalt source, and the manganese source may be 1:1, 1.5:1, 2:1, or any value between (1-2):1.
[0031] And / or, the alcohol solvent includes at least one of ethanol, propanol, and isopropanol; And / or, the mass ratio of the alcohol solvent to the water and the urea is 1.5:1:(1-1.5).
[0032] For example, the mass ratio of the alcohol solvent to the water and the urea may be 1.5:1:1, 1.5:1:1.1, 1.5:1:1.2, 1.5:1:1.3, 1.5:1:1.4, 1.5:1:1.5 or any value between 1.5:1:(1-1.5).
[0033] According to an embodiment of the present application, the temperature of the coprecipitation reaction is 70-95°C; For example, the temperature of the coprecipitation reaction can be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or any value between 70 and 95°C.
[0034] And / or, the coprecipitation reaction time is 2 to 5 hours; For example, the coprecipitation reaction time can be 2 h, 3 h, 4 h, 5 h or any value between 2 and 5 h.
[0035] And / or, when preparing the first intermediate, the method further comprises: continuously introducing an inert gas below the liquid surface of the reaction system, wherein the inert gas comprises at least one of nitrogen, argon, helium and neon.
[0036] Furthermore, the compound containing doping elements refers to a compound formed by the doping elements, such as the compound containing doping elements includes salts containing doping elements, oxides containing doping elements, acids containing doping elements, etc. For example, the compound containing doping elements can be Zr(CH3COO)4.
[0037] According to an embodiment of the present application, the lithium source includes at least one of LiOH, Li2CO3, CH3COOLi, Li2C2O4, LiF, and Li3PO4; Furthermore, the particle size of the lithium source used in the present application is micrometer-sized, and its particle size range is 3μm≤D 50 ≤8μm.
[0038] And / or, the molar ratio of the first intermediate to the lithium source is 1:(1.05-1.2).
[0039] For example, the molar ratio of the first intermediate to the lithium salt may be 1:1.05, 1:1.07, 1:1, 1:1.16, 1:1.2 or any value between 1:(1.05-1.2).
[0040] According to an embodiment of the present application, the first sintering treatment includes: sintering at a temperature of 300-600°C (for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or any value between 300-600°C) for 2-6h (for example, 2h, 3h, 4h, 5h, 6h or any value between 2-6h), and then sintering at 650-750°C (for example, 650°C, 680°C, 700°C, 750°C or any value between 650-750°C). sintering at a temperature of 800-950°C (for example, 800°C, 847°C, 850°C, 892°C, 900°C, 950°C or any value between 800-950°C) for 10-20h (for example, 10h, 11h, 11.5h, 12h, 15h, 20h or any value between 10-20h), and then reducing the temperature to room temperature; And / or, the heating rate of the first sintering treatment is 1-5°C / min, and the cooling rate of the first sintering treatment is 1-5°C / min; For example, the heating rate of the first sintering treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1 and 5°C / min, and the cooling rate of the first sintering treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1 and 5°C / min.
[0041] And / or, the first sintering process is performed in an oxygen atmosphere.
[0042] According to an embodiment of the present application, based on the mass of the second intermediate, the mass of the M element in the M2Se3 is 800-1500 ppm.
[0043] For example, based on the mass of the second intermediate, the mass of the M element in the M2Se3 can be 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm or any value between 800-1500 ppm.
[0044] Furthermore, the D of M2Se3 used in this application 50 ≤1μm.
[0045] According to an embodiment of the present application, the temperature of the second sintering treatment is 290-400° C., and the time of the second sintering treatment is 8-12 hours.
[0046] For example, the temperature of the second sintering process may be 290°C, 300°C, 350°C, 360°C, 380°C, 400°C or any value between 290-400°C.
[0047] For example, the time of the second sintering treatment can be 8 h, 9 h, 10 h, 10.5 h, 11 h, 12 h or any value between 8 and 12 h.
[0048] The second sintering process is performed in an air atmosphere.
[0049] The present application also provides a positive electrode active material, which is prepared by the preparation method of the positive electrode active material described above.
[0050] The present application also provides a lithium-ion battery, which includes the positive electrode active material described above.
[0051] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0052] 1. Preparation of positive electrode active materials Example 1 Embodiment 1 provides a method for preparing a positive electrode active material, comprising the following steps: 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0053] The corresponding masses of the first intermediate and lithium carbonate are weighed at a molar ratio of 1:1.07, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0054] 5 kg of the second intermediate and 8.13 g of In2Se3 (800 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0055] Example 2 Embodiment 2 provides a method for preparing a positive electrode active material, comprising the following steps: 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0056] The corresponding masses of the first intermediate and lithium carbonate are weighed at a molar ratio of 1:1.07, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0057] 5 kg of the second intermediate and 12.19 g of In2Se3 (1200 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0058] Example 3 Embodiment 3 provides a method for preparing a positive electrode active material, comprising the following steps: 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0059] The corresponding masses of the first intermediate and lithium carbonate are weighed at a molar ratio of 1:1.07, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0060] 5 kg of the second intermediate and 15.23 g of In2Se3 (1500 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was completed, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced throughout the sintering process. After cooling, the positive electrode active material was obtained.
[0061] Example 4 Embodiment 4 provides a method for preparing a positive electrode active material, comprising the following steps: 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0062] The corresponding masses of the first intermediate and lithium carbonate are weighed at a molar ratio of 1:1.07, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0063] 5 kg of the second intermediate and 16.20 g of Ga2Se3 (1200 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0064] Example 5 Embodiment 5 provides a method for preparing a positive electrode active material, comprising the following steps: Dissolve 1.75 mol (CH3COO)2Ni, 1.75 mol (CH3COO)2Co, and 1.5 mol (CH3COO)2Mn in 2.5 L deionized water at a molar ratio of 0.35:0.35:0.3 to form a main metal salt solution A; dissolve 1.56 g Zr(CH3COO)4 (1500 ppm) in 500 mL deionized water to form an auxiliary salt solution B; weigh 300 g propanol, 200 g deionized water, and 300 g urea, dissolve and mix to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively by a metering pump, and N2 was introduced below the liquid surface at the same time. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was turned on, and the mixed solution was heated to 90°C, and reflux was turned on. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, and washed alternately with deionized water and ethanol twice, and freeze-dried to obtain the first intermediate.
[0065] The first intermediate and lithium carbonate of corresponding mass are weighed at a molar ratio of 1:1.16, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 892°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0066] 5 kg of the second intermediate and 12.19 g of In2Se3 (1200 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 360°C at a rate of 2°C / min and kept at a constant temperature for 10.5 h. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0067] Example 6 Embodiment 6 provides a method for preparing a positive electrode active material, comprising the following steps: 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0068] The first intermediate and lithium carbonate of corresponding mass are weighed and mixed in a molar ratio of 1:1.07. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min at 450°C for 2h, 680°C for 2h, and 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, the mixture is crushed to obtain a second intermediate.
[0069] 5 kg of the second intermediate and 5.08 g of In2Se3 (500 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0070] Example 7 Embodiment 7 provides a method for preparing a positive electrode active material, comprising the following steps: 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0071] The corresponding masses of the first intermediate and lithium carbonate are weighed at a molar ratio of 1:1.07, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0072] 5 kg of the second intermediate and 20.31 g of In2Se3 (2000 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0073] Comparative Example 1 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5 L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 1.56 g Zr(CH3COO)4 (1500 ppm) was dissolved in 500 mL deionized water to form an auxiliary salt solution B; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A and solution B were added to solution C at a rate of 50 mL / min and 10 mL / min respectively using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A and solution B were added, radiation heating was started, and the mixed solution was heated to 90 ° C, and reflux was started. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, washed twice with deionized water and ethanol alternately, and freeze-dried to obtain the first intermediate.
[0074] The first intermediate and lithium carbonate of corresponding mass were weighed at a molar ratio of 1:1.07, and mixed. After mixing, they were transferred into a box furnace and sintered at a heating rate of 2°C / min, according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 was introduced throughout the sintering process. After the high-temperature sintering was completed, the temperature was lowered at a rate of 1°C / min, and after cooling to room temperature, it was crushed and the obtained product was used as the positive electrode active material.
[0075] Comparative Example 2 2.5 mol (CH3COO)2Ni, 1.5 mol (CH3COO)2Co, and 1 mol (CH3COO)2Mn were dissolved in 2.5L deionized water at a molar ratio of 0.5:0.3:0.2 to form a main metal salt solution A; 300 g propanol, 200 g deionized water, and 300 g urea were weighed and dissolved and mixed to form a base solution C. Solution A was added to solution C at a rate of 50 mL / min using a metering pump, and N2 was introduced below the liquid surface. Ultrasonic stirring was started at a speed of 500 r / min. After solution A was added, radiation heating was turned on, and the mixed solution was heated to 90°C, and reflux was turned on. After reflux for 3 hours, radiation heating was stopped, and N2 was kept introduced and stirred until the mixed solution cooled to room temperature. The obtained product was filtered, and washed alternately with deionized water and ethanol twice, and freeze-dried to obtain the first intermediate.
[0076] The corresponding masses of the first intermediate and lithium carbonate are weighed at a molar ratio of 1:1.07, and mixed. After mixing, they are transferred into a box furnace and sintered at a heating rate of 2°C / min. The high-temperature sintering is carried out in sequence according to the procedure of sintering at 450°C for 2h, sintering at 680°C for 2h, and sintering at 847°C for 11.5h. O2 is introduced throughout the sintering process. After the high-temperature sintering is completed, the temperature is lowered at a rate of 1°C / min. After cooling to room temperature, it is crushed to obtain a second intermediate.
[0077] 5 kg of the second intermediate and 12.19 g of In2Se3 (1200 ppm) were added to a high-speed mixer for dispersion and mixing. After mixing, they were transferred to a box furnace and heated from room temperature to 380°C at a rate of 2°C / min and kept at a constant temperature for 9 hours. After the constant temperature was reached, the temperature was lowered to room temperature at a rate of 1°C / min. Air was introduced during the entire sintering process. After cooling, the positive electrode active material was obtained.
[0078] 2. Performance Test 2.1 Physical properties test The first intermediate and the positive electrode active material prepared in Examples 1-7 and Comparative Examples 1-2 were tested by scanning electron microscope (SEM). Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 It can be seen that the method of the present application successfully synthesized a first intermediate having a petal-shaped, loose structure, and the primary particles of the positive electrode active material prepared by the method of the present application are slender, have a high aspect ratio, a large specific surface area, and a loose structure.
[0079] The specific surface area and particle size of the first intermediate prepared in Examples 1-7 and Comparative Examples 1-2 were tested. The specific test data are shown in Table 1 below.
[0080] 2.2 Electrochemical performance test The electrochemical performance of the positive electrode active materials prepared in Examples 1-7 and Comparative Examples 1-2 was tested, and the specific method was as follows: (1) Take the positive electrode active materials obtained in Examples 1 to 7 and Comparative Examples 1 to 2, and weigh three materials in a mass ratio of 96 (positive electrode active material): 2 (binder PVDF): 2 (conductive agent SP); (2) Add solvent NMP and disperse and mix evenly in a beaker to form a slurry, and then use a scraper to coat it on a conductive aluminum foil (surface density 20.0-22.0 mg / cm 2 ); (3) Place in a 120°C vacuum drying oven and dry for 2 hours, then cut into electrodes with a diameter of 14 mm, weigh them, and then vacuum bake at 120°C for 2 hours; (4) Assemble CR2025 button cells in a nitrogen glove box using lithium metal as the negative electrode; (5) Place the button cell into the Xinwei test system for charge and discharge testing at a constant temperature of 25°C.
[0081] The electrochemical performance test results of the positive electrode active materials of Examples 1-7 and Comparative Examples 1-2 are shown in Table 1 below.
[0082] Table 1 Summary of specific surface area and particle size data of the first intermediate and electrochemical properties of the positive electrode active material
[0083] From the specific surface area and particle size data listed in Table 1, it can be seen that the first intermediate synthesized satisfies 2.5 μm ≤ D 50 ≤3.5μm, BET≥18m 2 / g, the first intermediate has a large specific surface area, which is beneficial to Li + Diffusion and primary particle forming of the material can further generate a positive electrode active material with a rod-like morphology having an extremely high aspect ratio.
[0084] Table 1 lists the 0.1C first discharge capacity and 0.5C~5C rate discharge capacity of Examples 1~7 and Comparative Examples 1~2. It can be seen from Table 1 that the 5C / 0.1C capacity retention rate of Examples 1-7 is higher than that of Comparative Examples 1-2, and the 5C / 0.1C capacity retention rate of Example 1-5 is higher than that of Examples 6-7.
[0085] Specifically, the amount of In2Se3 added in Example 6 is 500 ppm, the amount of In2Se3 added in Example 1 is 800 ppm, and no In2Se3 is added to Comparative Example 1. The discharge capacity and 5C / 0.1C capacity retention rate of Example 6 are higher than those of Comparative Example 1 and lower than those of Example 1, indicating that too little addition of In2Se3 will affect the electrochemical performance of the battery.
[0086] The amount of In2Se3 added in Example 7 is 2000ppm, and the amount of In2Se3 added in Example 3 is 1500ppm. The discharge capacity and 5C / 0.1C capacity retention rate of Example 7 are slightly lower than those of Example 3, indicating that excessive addition of In2Se3 cannot improve the electrochemical performance of the battery. This may be because a large amount of In2Se3 coating will hinder electronic conductivity, thereby leading to a decrease in electrochemical performance.
[0087] The discharge capacity of Example 5 is lower than that of Examples 1-4 and Examples 6-7 because the content of the nickel source in Example 5 is lower.
[0088] Compared with Example 1, Comparative Example 1 was not coated with M2Se3, and the discharge capacity and 5C / 0.1C discharge capacity retention rate of Comparative Example 1 were lower than those of Example 1. The reason for the poor electrochemical performance of Comparative Example 1 is that there is no M2Se3 in the positive electrode active material of Comparative Example 1. M2Se3 is a two-dimensional layered compound. The special adjustable band gap structure of M2Se3 gives it good electronic conductivity. At high discharge current, good electronic conductivity helps the material capacity to be exerted and the capacity retention rate.
[0089] Compared with Example 2, Comparative Example 2 did not add the doping element compound Zr(CH3COO)4 during the preparation of the positive electrode active material, and the discharge capacity and 5C / 0.1C discharge capacity retention rate of Comparative Example 2 were lower than those of Example 2. The reason for the poor performance of Comparative Example 2 is that the positive electrode active material does not contain the doping element Zr. The doping element in the positive electrode active material can effectively widen the crystal layer spacing, support the layered structure and anchor it, and inhibit the expansion / contraction of the unit cell along the c-axis direction during the charge and discharge process, thereby ensuring the performance of the material at a high rate.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0091] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a positive electrode active material, characterized in that: include: Mixing a nickel source, a cobalt source, a manganese source, a compound containing a doping element, urea, an alcohol solvent and water, and performing a coprecipitation reaction to obtain a first intermediate, wherein the doping element in the compound containing a doping element includes any one of Zr, Al, W, Sr and B; The first intermediate is mixed with a lithium source and subjected to a first sintering treatment to obtain a second intermediate; The second intermediate is mixed with M2Se3 and subjected to a second sintering treatment to obtain a positive electrode active material, wherein M in the M2Se3 includes any one of In and Ga.
2. The method for preparing a positive electrode active material according to claim 1, characterized in that: Based on the total mass of the nickel source, the cobalt source and the manganese source, the added amount of the compound containing the doping element is 1000-3000 ppm.
3. The method for preparing a positive electrode active material according to claim 1, characterized in that: The nickel source includes any one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate; The cobalt source includes any one of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate; The manganese source includes any one of manganese sulfate, manganese nitrate, manganese chloride and manganese acetate; The molar ratio of nickel in the nickel source to cobalt in the cobalt source and manganese in the manganese source is x:y:(1-xy), wherein 0 <x≤0.60,0<y≤0.40; And / or, the ratio of the molar amount of the urea to the sum of the molar amounts of the nickel source, the cobalt source, and the manganese source is (1-2):1; And / or, the alcohol solvent includes at least one of ethanol, propanol, and isopropanol; And / or, the mass ratio of the alcohol solvent to the water and the urea is 1.5:1:(1-1.5).
4. The method for preparing a positive electrode active material according to claim 3, characterized in that: The temperature of the coprecipitation reaction is 70-95°C; And / or, the coprecipitation reaction time is 2 to 5 hours; And / or, when preparing the first intermediate, the method further comprises: continuously introducing an inert gas below the liquid surface of the reaction system, wherein the inert gas comprises at least one of nitrogen, argon, helium and neon.
5. The method for preparing a positive electrode active material according to claim 1, characterized in that: The lithium source includes at least one of LiOH, Li2CO3, CH3COOLi, Li2C2O4, LiF, and Li3PO4; And / or, the molar ratio of the first intermediate to the lithium source is 1:(1.05-1.2).
6. The method for preparing the positive electrode active material according to claim 5, characterized in that: The first sintering treatment includes: sintering at a temperature of 300-600°C for 2-6 hours, then sintering at a temperature of 650-750°C for 2-6 hours, sintering at a temperature of 800-950°C for 10-20 hours, and then reducing the temperature to room temperature; And / or, the heating rate of the first sintering treatment is 1-5°C / min, and the cooling rate of the first sintering treatment is 1-5°C / min; And / or, the first sintering process is performed in an oxygen atmosphere.
7. The method for preparing a positive electrode active material according to claim 1, characterized in that: Based on the mass of the second intermediate, the mass of the M element in the M2Se3 is 800-1500 ppm.
8. The method for preparing a positive electrode active material according to claim 7, characterized in that: The temperature of the second sintering treatment is 290-400° C., and the time of the second sintering treatment is 8-12 hours.
9. A positive electrode active material, characterized in that: The positive electrode active material is prepared by the method for preparing the positive electrode active material according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode active material according to claim 9.
Citation Information
Patent Citations
Ternary positive material and preparation method thereof
CN107394164A
Metal selenide / C / B compositely coated cathode material and preparation method thereof
CN109755513A
High-activity petal-shaped nickel-cobalt-manganese ternary precursor and preparation method thereof
CN110182857A
Nickel-cobalt-manganese-aluminum quaternary precursor, positive electrode material and preparation method thereof
CN113206242A
Porous nickel cobalt lithium manganate ternary positive electrode material and preparation method thereof
CN113213556A
